Gold nanograin microelectrodes for neuroelectronic interfaces. Issue 2 (9th November 2012) - Kim, Raeyoung; Hong, Nari; Nam, Yoonkey
Abstract Neuroelectronic interfaces are imperative in investigating neural tissues as electrical signals are the main information carriers in the nervous system and metal microelectrodes have been widely used for recording and stimulation of nerve cells. For high performance microelectrodes, low tissue‐electrode interfacial impedance and high charge injection limits are essential and nanoscale surface engineering has been utilized to meet the requirements for microelectrodes. We report a single‐cell sized microelectrode, which has unique gold nanograin structures, using a simple electrochemical deposition method. The fabricated microelectrode had a sunflower shape with 1–5 (m of micropetals along the circumference of the microelectrode and 500 nm nanograins at the center. The nanograin electrodes had 69‐fold decrease of impedance and 10‐fold increase in electrical stimulation capability compared to unmodified flat gold microelectrodes. The recording and stimulation performance of nanograin electrodes was tested using dissociated rat hippocampal neuronal cultures. Noise levels were extremely low (2.89 μVrms) resulting in high signal‐to‐noise ratio for low‐amplitude action potentials (18.6–315 μV). Small biphasic current pulses (20–60 μA) could evoke action potentials from neurons nearby electrodes. This new nanostructured neural electrode may be applicable for the development of cell‐based biosensors or clinical neural prosthetic devices.